2019
DOI: 10.1007/s00425-019-03292-2
|View full text |Cite
|
Sign up to set email alerts
|

Site-dependent induction of jasmonic acid-associated chemical defenses against western flower thrips in Chrysanthemum

Abstract: Main conclusion Local and systemic induction of JA-associated chemical defenses and resistance to western flower thrips in Chrysanthemum are spatially variable and dependent on the site of the JA application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
(75 reference statements)
2
14
0
Order By: Relevance
“…Additional correlational analysis between chlorogenic acid and PPO activity levels on a larger number of genotypes should be performed in future studies. Activation of JA signaling has been reported to enhance plant resistance to WFT in some plant species (Abe et al 2009;Chen et al 2018;Escobar-Bravo et al 2017;Li et al 2002), including chrysanthemum (Chen et al 2020). Our study further reveals that the effect of JA on chrysanthemum resistance to WFT is genotype-dependent (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Additional correlational analysis between chlorogenic acid and PPO activity levels on a larger number of genotypes should be performed in future studies. Activation of JA signaling has been reported to enhance plant resistance to WFT in some plant species (Abe et al 2009;Chen et al 2018;Escobar-Bravo et al 2017;Li et al 2002), including chrysanthemum (Chen et al 2020). Our study further reveals that the effect of JA on chrysanthemum resistance to WFT is genotype-dependent (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Taken together, the chemical or physical traits that contribute to JA-mediated induction of chrysanthemum resistance to WFT are still unknown. However, in a recent study, variations in JA-mediated induction of sugars and amino acids, as well as of defensive chemicals such as chlorogenic acid, coincided with differences in thrips susceptibility between young and old leaves of chrysanthemum plants (Chen et al 2020 ). These compounds could be targets for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One constraint in breeding plants to defend against plant herbivores and pathogens has generally been the need to combine several analytical methods to obtain an overview of total secondary metabolism (Wink 1988). Ecometabolomic analyses are excellent tools to advance the study of effective treatments against herbivorous pests in plants (Chen et al 2020). Chen et al (2020) recently reported that the application of jasmonic acid to all leaves or only the apical leaves of chrysanthemums (Chrysanthemum × morifolium) increased the resistance to thrips, whereas the application to basal leaves was not v www.esajournals.org effective against the thrip pest (Chen et al 2020).…”
Section: General and Significant Changes Observed In Metabolomic Analyses Of Plant Foliar Metabolism Related Tomentioning
confidence: 99%